THE "A" coatings " : selected peer-reviewed papers from the 14th International Conference 2020 "THE A COATINGS" : November 19-20, 2020, Nuremberg, Germany - Merklein, Marion; Bouzakis, Konstantinos Dionysios; Michailidis, Nikolaos; Denkena, Berend, 1959-; Bobzin, Kirsten (Trans Tech Publications, Ltd, 2020)
Selected peer-reviewed papers from the 14th International Conference 2020 ""THE A COATINGS"" Selected peer-reviewed papers from the 14th International Conference 2020 ""THE A COATINGS"", November 19-20, 2020, Nuremberg, Germany.
Keywords: Coatings -- Congresses.; elektronické knihy; electronic books